Avaliação funcional e histomorfométrica do intestino de Syrian Hamsters (Mesocricetus auratus) experimentalmente infectados com Lawsonia intracellularis - Fabio Augusto Vannucci (2009)
Severity of infection based on gross and microscopic lesions and immunohistochemistry was correlated with intestinal absorption and histomorphometry in syrian hamsters (Mesocricetus auratus) experimentally inoculated with Lawsonia intracellularis. Sixty hamsters between two and three weeks of age from a colony with no history of EP were used. The infected group (n=30) received, by gavage, 1 mL of intestinal mucosa homogenate from PE naturally infected pigs containing approximately 7,5 x 109 L. intracellularis organisms. The control group (n=30) received one mL of SPG by the same route. Animals were weighed at regular intervals of nine days to assess the weight gain. Twenty six days after inoculation, the intestinal absorption of glucose, sodium, potassium and chloride was evaluated for 40 minutes, in intervals of 10 minutes. In this procedure, a standard solution was infused in the cranial jejunum and collected in terminal ileum. The experimental infection was confirmed by gross and histopathological examination and L. intracellularis antigen labelling by IHC. Histomorphometry showed elongation of villous and deepening of intestinal crypts in hamsters that had high infection level as demonstrated by IHC. These animals had significant lower intestinal absorption of glucose, potassium and chloride (p<0,05), when compared to uninfected controls. These results indicate a lower intestinal absorption as being an important mechanism of diarrhea in L. intracellularis experimentally infected hamsters. Therefore, the diarrhea for malabsorption should be considered as the main mechanism involved in the pathophysiology of diarrhea in the EP